The influence of the spokesperson’s skills (media person) in managing tourism crises (An exploratory study of a sample of the shrines of Babil Governorate) - ABD ALRASOOL, EBRAHEM; HAMID JAMAL, DINA (International Journal of Psychosocial Rehabilitation, 2020)
The media spokesperson is the interface between the organization and the public and plays an important role in times of crisis by sending reassuring messages to the public or determining levels of warning and readiness for what might plague the organizations in general and tourism in particular. All that the media spokesperson had high skills to enable him to deal with crises With all his wisdom, for the purpose of overcoming it and putting the organization in a better position than it was before the occurrence of the crisis, as the researcher identified the problem of the study through the following question (What is the role of the media spokesperson in managing the tourism crises through the study sample?) and the descriptive analytical approach was adopted in carrying out this research, This study included (the private secretaries, the deputies of the private secretaries), as the study population intended included 54 people who had the questionnaire form distributed to them, and the forms were collected in the final form to be 50 valid forms, as the questionnaire consisted of 80 paragraphs. The questionnaire was supported by field interviews and coexistence, and in this study it was based on the (SPSS V.23) program as well as the (AMOS V.23) program, in addition to descriptive statistics methods. As for the purpose of testing hypotheses, perhaps the most important conclusions reached by the study are the existence of a significant correlation relationship between the skills of the media spokesperson and the management of tourism crises, as well as the existence of a weakness between self-skills and the containment of damages in the researched organization. As a result, the study concluded with several conclusions, perhaps the most important of them Every shrine should have an official spokesman for the shrine with media skills that enable him to interact with the public in times of crisis.